How do we classify organ involvement in Chagas disease? A systematic review of organ involvement since 1909, Highlighting the urgent need for a universal classification system in Chronic Chagas disease. - Irene Losada Galván; Magdalena García; Alejandro Marcel Hasslocher-Moreno; Ariadna Ortiga; Sergi Sanz; Israel Molina; Joaquim Gascón; Maria-Jesus Pinazo (Public Library of Science (PLoS), 2024)
Chagas disease (CD) is recognized as one of the 20 neglected tropical diseases by the World Health Organization (WHO), posing a significant global health challenge. The objective of this work was to conduct a systematic methodology review to explore the different classifications used to describe the presence and degree of organ involvement in patients with CD since the disease's description in 1909. We searched relevant electronic medical databases from their inception dates to July 2023. We also delved into historical variations and revisions of each classification, the necessary diagnostic methods, their prognostic value, and their uptake. Our study underscores the conspicuous absence of a universally accepted CD classification system for cardiac and digestive involvement, both in the context of clinical trials and within current clinical guidelines. This endeavour will facilitate cross-population comparisons if clinical manifestations and complementary test results are available for each patient, constituting a pivotal stride toward identifying precise prognoses and establishing a minimum data set requisite for a fitting CD classification, tailored to the test availability in both endemic and non-endemic regions.